Redox regulation of the calcium activated and voltage gated potassium channel, BK: shaping the pancreatic beta cells action potential and calcium influx - Curry, Liam (2019)
Large conductance calcium activated potassium channels (BK) are ubiquitous in the membranes of all excitable cells and are responsible for limiting action potential propagation and cell function by hyperpolarising action potentials, there is evidence that BK channels are important for the function of pancreatic β cells. Hydrogen peroxide (H2O2) is a reactive oxygen species commonly found in all cell types and known to have an effect on BK channels. In this study electrophysiology and fluorescence imaging were used determine the effect of hydrogen peroxide on BK channel activity and action potential shaping. In single-channel patches BK channels were activated by hydrogen peroxide with a bell-shaped relationship, 1 µM H2O2 was shown to be the most stimulatory concentration, identified by a 1000-fold increase in open channel probability (p = 0.0280). From whole-cell recordings, carried out to confirm activity across the whole cell and measure the voltage dependent effects, it was shown that this was a universal effect across the entire cell membrane with a 24% increase in potassium current amplitude (p = 0.0224), the effect of hydrogen peroxide acting on BK was confirmed by the blockers quinine and paxilline. Inside-out patch showed that hydrogen peroxide acted directly on channels to stimulate channel opening (p = 0.0141). Current-clamp recordings showed that hydrogen peroxide had no significant effect on the shape of action potentials in terms of baseline membrane potential, peak amplitude; half-width and maximum rate of decay of spiking, stimulated by 2.5 and 10 mM glucose. Through calcium imaging it was observed that H2O2 had no significant effect on calcium influx. It was concluded that although hydrogen peroxide directly activates BK channels in β cells, this effect is insufficient to alter the shape of glucose-stimulated action potentials or calcium influx.